Keefektifan Teknik Sosiodrama Untuk Mengurangi Perilaku Agresif Verbal Siswa Kelas VII di SMP Negeri 5 Kepanjen - Vony Aristya Sari; Blasius Boli Lasan; Eva Kartika Wulan Sari (JKI (Jurnal Konseling Indonesia), 2017)
Delivery of words and verbal sentences are mental or psychological harm someone who was the target of an aggressive, such as snap, insult, humiliate, cursing, mocking, angry, and threatens. The use of the technique of sosiodrama aims to develop students ' cognitive and affective aspects so that in addition to studying the behavior of new students also have an understanding of good behavior and less good. This research aims to find out if the technique sosiodrama effective to reduce aggressive behavior in verbal students. The subject in this study amounted to 11 children. The method used is an experiment with the design of one group pretest – posttest design. The collected data is analyzed with a Wilcoxon. The results showed an average pretest score of 135.5 categories include very high, while the average scores posttest of 106.6 categories include medium, means there is a decrease. Wilcoxon test obtained based on the value significance of 0.003 0.05 sosiodrama technique < effective to reduce aggressive behavior in Junior High School students verbal Country 5 Kepanjen.